Development of an Information Website as a Publication Medium for the Malikussaleh Airport Organizing Unit in Lhokseumawe - Raihansyah, Khananda; Asrianda; Muhammad Fikry (Teewan Journal Solutions, 2025)
Malikussaleh Airport currently uses social media such as Instagram to share information, which results in limited information accessibility for visitors regarding news, profiles, and airport activities. This study aimed to develop a website-based information system to facilitate employees in disseminating information and ease public access to updated airport news. The system was built using PHP programming language, MySQL database, and designed through Data Flow Diagrams (DFD). The implementation produced an informative and accessible platform that allows the airport management to provide transparent news, flight updates, and activity galleries. The results showed that the website effectively improved the information distribution process compared to previous social media-only methods.